Analisis Pengembangan Karir Pegawai Pada Lembaga Pendidikan - Khairunnisa, Khairunnisa; Wahyudin, Achmad; Zohriah, Anis (Program Studi Manajemen Pendidikan Islam Fak. Ilmu Tarbiyah dan Keguruan, 2023)
Career development for employees in educational institutions is crucial in advancing the quality of education in the era of globalization and constant change. This article discusses various aspects of career development, including training, continuous education, mentoring, performance evaluation, promotions, collaboration, networking facilitation, as well as rewards and recognition. This research employs a literature review method to analyze the contributions and challenges in the career development of employees in educational institutions. The findings indicate that relevant and tailored training, continuous education, effective mentoring, and performance evaluation can motivate employees to enhance the quality of education. However, a thoughtful approach to promotions and collaborations and building strong networks is necessary to support holistic career development. Rewards and recognition can also motivate staff but need to be managed wisely. To create a better future for education, educational institutions should consider effective strategies for employee career development.